Women and Men in Computer Science: Geeky Proclivities, College Rank, and Gender in Korea. Issue 1 (1st March 2018) - Kim, Hyomin; Cho, Youngju; Kim, Sungeun; Kim, Hye-Suk
Abstract: The underrepresentation of women in computer science (CS) is an extensively reported phenomenon. The institutional culture of "geek" masculinity has been recognized as one of the important factors in explaining women's avoidance of CS in Western contexts. We conducted a survey and in-depth interviews to examine how Korean CS majors interpret their departmental culture and form a sense of belonging. To summarize our findings, Korean students' identification of themselves with geekiness was associated with university prestige more frequently than with gender. The geek identities and practices often associated with masculinity in Western contexts are related to university prestige in Korea. We do not argue that gender is irrelevant in constructing students' practices and identities in CS. Instead, we argue that it is important to analyze how gender appears more or less noticeably in the discursive construction of CS professional identities depending on contexts. This study calls for more careful attention to the processes through which the constructed symbolic hierarchies of geek over nongeek are mediated by unequal structures, including but not limited to gender, in CS. Our findings suggest that gendering in and of CS is more complicated than the dichotomy of male-technical versus female-social stereotypes.